ATM signalling in perspective - Au, T. A. (T. Andrew); Electronics and Surveillance Research Laboratory (Australia) (Salisbury, S.A. : DSTO Electronics and Surveillance Research Laboratory, 1998)
Signalling has great impact on the efficient use of network resources, and the services that an Asynchronous Transfer Mode (ATM) network can offer. Importantly, signalling allows the transfer of service-related information in real time between the user and and the network, and among network entities to establish, maintain and release end-to-end virtual connections. For each particular signalling function, the corresponding procedures are defined such that the sequence and message format are specific to the network interface across which the exchange of signalling information takes place. This report reviews the signalling architectures for the user-network interface and the network-network interface in both private and public ATM network environments. It is hoped that readers will gain a proper perspective of the signalling protocols involved in ATM networks, and thereby an appreciation of their significant contributions.
"May 1998"--T.p. verso.
"AR-010-539"--Cover.
Available in PDF format via the World Wide Web.
Keywords: Asynchronous transfer mode; Signal theory (Telecommunication)